2011
DOI: 10.1186/1471-2458-11-694
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis resurgence in Toronto, Canada: a population-based study including test-incidence feedback modeling

Abstract: BackgroundPertussis continues to challenge medical professionals; recently described increases in incidence may be due to age-cohort effects, vaccine effectiveness, or changes in testing patterns. Toronto, Canada has recently experienced increases in pertussis incidence, and provides an ideal jurisdiction for evaluating pertussis epidemiology due to centralized testing. We evaluated pertussis trends in Toronto using all available specimen data, which allowed us to control for changing testing patterns and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 35 publications
(57 reference statements)
4
51
0
5
Order By: Relevance
“…1,3 However, since WPVs were replaced by purified APVs in many developed countries in 1980s/1990s, a resurgence of pertussis has been observed in these countries with high vaccination coverage in the past 10 y 11,[19][20][21] The incidence of pertussis among children who were born and vaccinated during the transition to purified APVs have found that the rate of infection is significantly higher among children who have been vaccinated with only APVs compared with those who have been vaccinated with even a single dose of the WPVs. 22 In contrast, in countries where co-purified APVs are used in the national immunization program e.g., Japan and China, the accumulating epidemiological evidence suggests that co-purified APVs may be achieving more consistent population protection, in fact a lower pertusiss incidence is noted in China according to the official report.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 However, since WPVs were replaced by purified APVs in many developed countries in 1980s/1990s, a resurgence of pertussis has been observed in these countries with high vaccination coverage in the past 10 y 11,[19][20][21] The incidence of pertussis among children who were born and vaccinated during the transition to purified APVs have found that the rate of infection is significantly higher among children who have been vaccinated with only APVs compared with those who have been vaccinated with even a single dose of the WPVs. 22 In contrast, in countries where co-purified APVs are used in the national immunization program e.g., Japan and China, the accumulating epidemiological evidence suggests that co-purified APVs may be achieving more consistent population protection, in fact a lower pertusiss incidence is noted in China according to the official report.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory methods have been previously described. [15][16][17] Briefly, until May 28, 2012, primers targeting the insertion sequence IS481 were used to detect B. pertussis. Following this date, primers targeting a 50-base pair segment of the recA gene were also included to distinguish B. pertussis from Bordetella holmesii.…”
Section: Laboratory Datamentioning
confidence: 99%
“…A different situation was noted in the United States where from 2004 to 2010 over 90% of severe complications and deaths recorded due to pertussis concerned infants ≤ 3 months old [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%